MOLECULAR GENETIC CHARACTERISTICS OF ALLELE VARIANTS OF MICROSATELLITE LOCI DU281, DU215, AND DU323 IN THE PARTHENOGENETIC LIZARDS DAREVSKIA ROSTOMBEKOVI (FAMILY LACERTIDAE) - Osipov, F A; Vergun, A A; Girnyk, A E; Kutuzova, N M; Ryskov, A P (Molekulârnaâ genetika, mikrobiologiâ i virusologia, 2016)
One of the main questions-in the study of the unisexual (parthenogenetic) species of vertebrates is the determination of their genetic diversity. Nuclear and mitochondrial genetic markers can be used for this purpose. One of the most effective genetic markers is the microsatellite DNA, which mutates at a high rate. Development and characteristics of such markers are necessary in studies of parthenogenetic species. In this work, the analysis of the allele polymorphism of three microsatellite loci was performed for the first time via locus-specific PCR in the populations of parthenogenetic species Darevskia rostombekovi (n = 42) and bisexual parental species D. raddei (n = 6) and D. portschinskii (n = 6). All examined individuals of the parthenogenetic D. rostombekovi were heterozygous. Two to five alleles, depending on the locus, were found in the studied populations of the parthenogenetic species. It was shown that the differences were due to the varying structure of the microsatellite cluster and to single nucleotide substitutions at fixed distances in the DNA regions adjacent to the cluster. The allele structure variations form haplotype markers specific for each allele and inherited from the parental bisexual species. It was determined which alleles of the parthenogenetic species were inherited from the maternal species and which from the paternal species. Characteristics of distribution, frequency of occurrence, and combination of alleles of microsatellite loci, which determine the distinctive features of each D. rostombekovi population were obtained. The data can be used in the future to determine the clonal diversity and possible ways of its formation in the populations of the parthenogenetic species D. rostombekovi.